Integrating spatial-temporal soundscape mapping with landscape indicators for effective conservation management and planning of a protected area - Xu, Xiaoqing; Baydur, Caner; Feng, Jingjie; Wu, Chengzhao (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2024)
Protected areas (PAs) possess generous biodiversity, making them great potential for human and wildlife wellbeing. Nevertheless, rising anthropogenic sounds may pose a serious challenge and threat to the habitats. Therefore, understanding the acoustic environments of PAs and implementing proper conservation strategies are essential for maintaining species richness within the territory. In this study, we investigate the spatial-temporal variations of soundscape distribution in the Dashanbao Protected Area (DPA) of China, ultimately discussing the planning and management strategies. Firstly, to systematically analyse the spatial-temporal soundscape distribution of the reserve, we generated single and multi-acoustic source maps by classifying geographical, biological, and anthropogenic sounds. In the region, we installed 35 recording points and collected sounds using the synchronic recording method. Secondly, we conducted Spearman correlation analyses to examine the relationships between the sound sources and i) temporal variations, ii) landscape feature indicators. Thirdly, we identified the dominant sound sources in the region and their conflict areas through the cross-analysis module of Grass Geographic Information Systems (GIS). Finally, we provided sound control strategies by discussing landscape indicators and land-use management policies. The results show that even though there is conservation planning in the DPA, anthropogenic sounds dominate in certain parts of the reserve depending on diurnal and seasonal cycles. This reveals deficiencies in the DPA's current planning concerning the soundscape and highlights the effectiveness of spatial-temporal mapping. Additionally, our correlation analyses demonstrate that landscape feature indicators can represent how sound environment is affected by landscape. The patch diversity (PD), landscape shape index (LSI), Shannon's Diversity Index (SHDI), woodland, shrubland, and water distance (WD) were identified as the primary predictors for both biological and anthropogenic sounds. None of the indicators exhibited a significant positive or negative correlation with geological sounds. Consequently, to enhance and conserve the acoustic quality of the region, spatial-temporal mapping with landscape indicators can be employed in the management and planning processes.
Keywords: Spatial -temporal mapping; Soundscape; Protected area; Landscape feature indicators; Land -use; Conservation management and planning; LOW-FREQUENCY SONGS; NOISE-POLLUTION; SPATIOTEMPORAL VARIABILITY; BIODIVERSITY; PERFORMANCE; MODEL; GIS; ACCEPTABILITY; METHODOLOGY; MIGRATION; Environmental Sciences & Ecology